Técnicas de animación de la lectura y su aporte en los procesos áulicos de los estudiantes de la Escuela de Educación Básica Octavio Gerardo Icaza, cantón Urdaneta, provincia los Ríos. - Muñoz Obando, Gladys Janeth (2017)
The present final report consists of the techniques of animation of the reading and its contribution in the academic processes of the students of the Basic Education School "Octavio Gerardo Icaza" of the Urdaneta Canton, Province of Los Ríos; the same as in this case will be applied in the aforementioned institution; which will provide all the necessary facilities for the application of the research instruments in such a way that all the necessary procedures for the investigative process can be executed in an integral manner. This is of the utmost importance because it seeks to create committed readers with a willingness to read. However, it seems that the practices of some homes and educational institutions do not aim to allow students to see reading as a possibility beyond understanding a text. It should be considered that these practices can also lead to seeing the reading from the enjoyment and intimate and personal enjoyment to know deferential possibilities to understand and perceive the world that surrounds them.